Burden of drug use disorders from 1990 to 2021 and projection to 2050 in China: findings from the 2021 global burden of disease study - Yu, Shuzheng; Chen, Yanting; Huang, Shaohua; Wang, Bing; Wu, Qingrong (Frontiers in Pharmacology, 2025)
BackgroundDrug use disorders (DUDs) represent a major public health challenge globally, including China. This study investigated the impact of DUDs in China over the past 3 decades and examined the long-term trends in their epidemiological characteristics.MethodsData were obtained from the 2021 Global Burden of Disease (GBD) study. The burden of DUDs was assessed through Disability-Adjusted Life Years (DALYs), Years of Life Lost (YLLs), and Years Lived with Disability (YLDs). Joinpoint analysis was used to compute the Average Annual Percentage Change (AAPC), and Age-Period-Cohort analyses were conducted to illustrate trends in the burden of DUDs. A Bayesian Age-Period-Cohort model was fitted to forecast the anticipated burden.ResultsFrom 1990 to 2021, the Age-Standardized Incidence Rate (ASIR), Age-Standardized Prevalence Rate (ASPR), and Age-Standardized Mortality Rate (ASMR) for DUDs in China demonstrated a consistent decline, with AAPC values of −0.76% (95% confidence interval [CI]: 0.83% to −0.69%), −1.05% (95% CI: 1.25% to −0.84%), and −4.41% (95% CI: 4.75% to −4.08%), respectively. Analysis of temporal trends indicated that the ASIR and ASPR for DUDs peaked between 1990 and 2000, followed by a variable decline, with a minor uptick noted from 2015 to 2021. The age-standardized DALY rates reached their zenith during 1990–2000. Additionally, analysis by age group indicated that from 1990 to 2021, the ASIR and ASPR for DUDs were highest among individuals aged 20–24 years, followed by a fluctuating decline. Gender-based analysis indicated that throughout this period, disease burden indicators for males consistently surpassed those for females. Projections from the Bayesian Age-Period-Cohort model suggest the ASIR will increase by 3.91% annually from 2022 to 2050, with growth rates of 4.54% for males and 3.25% for females.ConclusionBetween 1990 and 2021, China experienced a decline in the overall burden of DUDs. However, high incidence and prevalence rates persist, signifying an ongoing significant impact. By 2050, both incidence and prevalence rates of drug abuse are expected to increase significantly, necessitating a focus on the male population and the development of targeted prevention and intervention strategies.